Gilt in the gust of Kong Kong reinvigoration the identity of sustainable eco-fishing village / Shaddam Shah Putra Mohd Suharto and Alamah Misni - Mohd Suharto, Shaddam Shah Putra; Misni, Alamah (College of Built Environment, 2023)
Kong Kong is administered by Pasir Gudang Municipal Council (Majlis Perbandaran Pasir Gudang) and managed by Head Village, Mr. Zulkhairi bin Mason.